Analysis of cerebral blood flow in Parkinson's disease with dementia versus subcortical ischemic vascular dementia using single photon emission computed tomography. Issue 4 (18th November 2014) - Kim, Tae‐Won; Chung, Yong‐An; Song, In‐Uk; Lee, Kwang‐Soo
ABSTRACT Since both Parkinson's disease with dementia (PDD) and subcortical ischemic vascular dementia (SIVaD) are subcortical dementia syndromes and have similar patterns of cognitive dysfunction, it is difficult to accurately differentiate between these in their early phases using neuropsychological tests. The purpose of this study was to investigate differences in the cerebral perfusion pattern of patients with SIVaD and PDD at the earliest stages using single photon emission computed tomography (SPECT). We, consecutively, recruited 24 patients with mild PDD, 28 patients with mild probable AD, and 33 age‐matched healthy subjects. All subjects underwent Tc‐99m HMPAO perfusion SPECT and general neuropsychological tests. Brain SPECT images were analyzed using the statistical parametric mapping program. There was more significant hypoperfusion in the right cuneus, fusiform gyrus and lingual gyrus in the occipital lobe, right middle temporal gyrus, right postcentral gyrus, and right cerebellar tonsil in PDD compared with the SIVaD group. Conversely, significant hypoperfusion was observed in the bilateral brain stem, limbic system and posterior cingulate gyrus in SIVaD compared with the PDD group. This study suggests that parieto‐occipital hypoperfusion in PDD and hypoperfusion of the brain stem and limbic system in SIVaD are likely useful to differentiate between mild PDD and SIVaD.